Investigating the role of rattan in development: CIFOR research into forest livelihood strategies and the dynamics of forest-related development projects in Indonesia - Belcher, B. (1999)
Efforts to develop non-timber forest products such as rattan need to consider the dynamic socio-economic context. Changing opportunities and constraints will have an important influence on wether the development is successful and what impacts are achieved. CIFOR, a centre within the CGIAR system, is researching this issue, focussing on a traditional rattan cultivation system in East Kalimantan, Indonesia. The research is investigating the direction and implications of this change on small holder forest management and forest product use